Innovation in Global Green Technologies 2020 - Sabban, Albert (IntechOpen, 2020)
In the last fifty years, the Earth has experienced rapid changes in climate, increasingly severe droughts, rising seawater levels, seawater acidification, increased depletion of groundwater reserves, and global rise of temperature. Green technologies for recycling waste, particularly electronic waste, which is increasing at an alarming rate, may be a potential solution to environmental pollution. Divided into three sections, this book presents comprehensive information on green technologies. Section 1 presents innovations in green electronic technologies, Section 2 discusses recycling and waste management, and Section 3 discusses innovation and economics in global green technologies.